Exponential estimates of a class of time-delay nonlinear systems with convex representations - Ramírez, Máximo; Villafuerte, Raúl; González, Temoatzin; Bernal, Miguel (Zielona Góra: Uniwersytet Zielonogórski)
This work introduces a novel approach to stability and stabilization of nonlinear systems with delayed multivariable inputs; it provides exponential estimates as well as a guaranteed cost of the system solutions. The result is based on an exact convex representation of the nonlinear system which allows a Lyapunov-Krasovskii functional to be applied in order to obtain sufficient conditions in the form of linear matrix inequalities. These are efficiently solved via convex optimization techniques. A real-time implementation of the developed approach on the twin rotor MIMO system is included.
Keywords: exponential estimates; time delay systems; TS model; guaranteed cost; convex representations